أحكام القرآن ازجلال الدین قادریؒ اور چودہری نذر محمدؒ کےمنہج واسلوب :تقابلی مطالعہ: A comparative study of the method and style of the late "Ahkam al-Qur'an" by Jalaluddin Qadri and Chaudhry Nazar Muhammad - Muneeb Masoud; Dr. Ashfaq Ali; Dr. Abdul Haq (International Research Journal of Arabic and Islamic Studies, 2024)
We as a Muslim, have a very rich history of exegetical works. The commentaries of Holy Quran further divided in sub topics with the passage of time. One of its type commonly known as “Jurisprudent Commentary” or “Tafsir-e-Fiqhi” deals with the Sharia rules stated in the Holy Quran. The same type is commonly known as “Ahkam-Ul-Quran” now a days, which only discussed the verses which deals Islamic jurisprudence. Many famous Scholars of Islamic history wrote well known commentaries on this topic. In Urdu language we don’t have Extensive storage, still few very important works came into existence. Ahkam-Ul-Quran written by Muhammad Jalal-Ul-DeenQadri, (a famous Islamic Scholar of the last century) is one of those commentaries. Qadri’s work surrounds the famous Quranic topic “Ahkam” discussing the permitted and prohibited acts in detail. We are not only collecting data about its introduction but this article unfolds the writing style of the said book along with comparison to another Urdu text of the same discipline known as “Ahkam-Ul-Quran by ChoudaryNazar Muhammad” who is founder of famous Pakistani Shoes Company “Servis”.One of them is famous religious Scholar while the other one is famous tycoon of Pakistan industry. We will find the differences between these works and the factors which made the difference.